The design and implementation of COSEN, an iterative algorithm for fully 3-D listmode data. - Levkovilz, R. (IEEE Transactions on medical imaging)
Presents coincidence-list-ordered set expectation-maximisation (COSEM), an algorithm for iterative image reconstruction directly from list-mode coincidence acquisition data. The COSEM algorithm is based on the ordered sets EM algorithm for binned data but has several extensions that makes it suitable for rotating two planar detector tomographs. The authors develop the COSEM algorithm and extend it to include analytic calculation of detection probability, noise reducing iterative filtering schemes, and on-the-fly attenuation correction methods. The authors present an adaptation of COSEM to the VaricamVG camera and show results from clinical and phantom studies.